Perilaku Muyek : Wujud Representasi Homoseksual di Pesantren (Analisis Ketidakadilan Gender Pada Pelaku Lesbian di Kalangan Santri) - Siti Syamsiyatul Ummah (PAX HUMANA, 2020)
AbstractSantri is a term usually applied to someone who studied in the boarding school. Generally, santri falls into the teenage category. Which at this time is a period of self-discovery and maturity of the sex organs that propels on the desire to love and be loved. The research sought to uncover gender injustice in lesbian behavior in boarding school. Or in other terms in boarding school is commonly called by “muyek”. This research is a qualitative case study with the location of one of the big boarding school in sumenep district, madura. The data retrieval is done by using in-depth interview techniques and observations conducted over a period of two months with a month of pre-research. The results of this research; the first is the presence of a partner that tends to be superior and monopolizing the relationship. The second, it stems from gender injustice on the inferior side that is harmful both biologically, physically, and materially.Keyword: Santri, Muyek, Gender Injustice